Oral and Craniofacial Anomalies of Fraser Syndrome: Prosthetic Management - Amornvit, P.; Rokaya, D.; Sapkota, D.; Sanohkan, S. (Kathmandu University Medical Journal, 2022)
Fraser syndrome (FS, MIM 219000) is a rare autosomal disorder characterized by systemic and oro-facial malformation, usually comprising cryptophthalmos, laryngeal malformations, syndactyly, and urogenital defects. We presented a 21-year-old FS case with partial missing teeth seeking aesthetic dental treatment. Clinical examination revealed bilateral cryptophthalmos, extensive syndactyly of hands and feet broad nose with the depressed nasal bridge, and surgically corrected bilateral cleft lip. She presented class III jaw relation and reduced the vertical height of the face. Prosthetic rehabilitation of the patient was done with upper and lower overlay dentures made from acrylic resin (VIPI BLOCK TRILUX®, VIPI Industria, Pirassununga, SP, Brazil) using computer-aided design (CAD) and computer-aided manufacturing (CAM) process. At the follow-up visit, the patient presented improved aesthetics and function. Proper management and rehabilitation of FS patients are challenging, but standard guidelines for oral health management are currently lacking. This article presents a case of Fraser syndrome presenting oral and craniofacial anomalies, and prosthetic rehabilitation was done. We also provided recommendations for the optimal oral health care for the FS patients. Functional adaptation and rehabilitation have significant roles in the various functions, survival, and quality of the life of FS patients. Integrated medical-dental care is needed in such patients with support from family members, friends, and colleagues.